EXPERIMENTAL STUDY EMBRYO LEAD ACETATE COMBINED WITH GOLD NANOAKVAHELAT - Savenkova О.О. (World of Medicine and Biology, 2013)
Among modern studies nanobiotechnologgy very small part of them devoted to studying the influence of various nano on embryogenesis and organogenesis. The aim of the study was to design teratogenic effects of lead acetate on the course of embryogenesis, as well as finding new bioantogonism lead. An experimental study in rats was selected. In experimental models used acetate and lead citrate gold obtained by akvananotehnology. The combined administration of low doses of lead and nanogold observed a significant increase in the number of corpora lutea of pregnancy, number of live fetuses, indicating their bioantagonism.